A base nacional comum curricular (BNCC) e a aplicabilidade de sistemas de equações lineares - DIAS, Flavione Lopes (2023)
This work aims to show that we can solve problems involving other areas of knowledge: Chemistry, Physics, Geography through applications of systems of linear equations. With this, the National Common Curricular Base (BNCC) was used, which brings the study of these systems in high school. The research made use of a bibliographic review from the studies of: Boldrini (1980), Dante (2016), Lezzi (2016), Lipschutz (2011) and Ruggiero and Lopes (1996). The results found in the bibliographic research were of fundamental importance, because, through the activities demonstrated, it was possible to observe that we can relate the teaching of mathematics to other areas of knowledge.